ZIS (Zakat, Infak, Sedekah) Financial Management for Health Programs at BAZNAS BAZIS DKI Jakarta - AlJannah, Eine Kiswah; Ciptaningtyas, Ratri; Nurmansyah, Muhammad Iqbal; Kusumawardani, Riastuti; Ariyanti, Fajar; Amelia, Erika (Faculty of Health Sciences, Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Philantrophy is an activity that viewed as supporting tool to elevate community healthy. Islamic philantrophy, such as Zakat,Infaq,Shadaqah(ZIS) has been a method to help low economic people but the allocation to health sectors is not well studued. This study aims to reveal the financial management of ZIS at BAZNAS BAZIS DKI Jakarta for their Health Program “Jak B Sehat”. This research is qualitative with an intrinsic case study. Data collection was conducted by in-depth interviews from 3 BAZIS employees and 2 beneficiaries, and document review. In general, financial management at BAZIS DKI is well executed because it has demonstrated a lawful source of funds, the financing management mechanism is carried out according to Shari'a, and the allocation of funds has a high impact on beneficiaries. However, there are obstacles that create less efficient task, such as technical problems and a lack of human resources. Jak B Sehat as a result of the financial management process has a positive impact among the beneficiaries, such as removing tatoos and ambulance delivery. Therefore, more human resources number is recommended to avoid double tasks and accelerate ZIS collection.Keywords: ZIS Financial Management, Jak B Sehat